Internacionalização da educação: uma análise política baseada no benchmark australiano - FARIA, Cristina Elsner de (My University, 2020)
O objetivo do artigo é analisar o processo histórico de formulação e implementação da política australiana para internacionalização da educação. Foi discutida a trajetória percorrida pela Austrália com o objetivo de extrair lições aprendidas para a formulação de políticas públicas e para a definição de arranjos estratégicos de articulação público-privada. Para tanto, a metodologia utilizada foi de pesquisa em documentos e relatórios internos do Ministério de Educação do Governo Federal Australiano, assim como de instituições representativas de referência no país.

The aim of this article is to analyze the historical process of formulating and implementing the Australian policy for internationalization of education. The path taken by Australia was discussed in order to extract lessons learned for the formulation of public policies and for the definition of strategic arrangements for public-private articulation. Hence, the methodology used consisted on the search of documents and internal reports from the Department of Education, Skills and Employment of the Australian Federal Government as well as representative institutions of reference in the country.
Internationalization of education: a policy analysis based on the Australian benchmark
Keywords: Intercâmbio educacional internacional; Austrália; Gestão e Negócios